ASHTVIDHA SHASTRA KARMA WITH SUTURING IN DETAIL (International Journal of Ayurveda and Pharma Research, 2019)
Ayurveda is considered by many scholars to be the oldest healing science. In sanskrit, Ayurveda means the Science of life. Ayurvedic knowledge originated in India more than 5000 years ago and is often called the Mother of healing. Ancient surgical science- Shalya Tantra is one of the vital components of Ayurveda science which involves surgical and para-surgical interventions. The Shalya chikitsa deals with different surgical approaches for the management of various diseases such as Bhagandra, Pilonidal sinus, Arshas etc. Shalya Tantra embraces all processes aiming at the removal of factors responsible for producing pain or misery to the body or mind. Acharya sushruta has mentioned Trividha Karma and Ashtavidha Shastra Karma as versatile approaches for therapeutic purposes. The concept of Ashtavidha karma is a unique contribution of Acharya Sushruta. These eight specific surgical procedures are useful in the management of all the diseases which require surgical intervention. In the present time though modern surgery has developed a lot but the basic procedures used in major conditions remained same. These eight basic surgical procedures mentioned by Sushruta are equally applied even today with required modifications to manage the diseases which require surgery including surgical emergency conditions. This article summarizes role of Ashtvidha Shastra Karma in Shalya karma for the management of various surgical problems.